Schizophrenia and the Self: Rebuilding and Maintaining Identity After a Diagnosis of Schizophrenia - Schweizer, Richard (2016)
Schizophrenia is a debilitating mental illness that strikes approximately 1 in 100 people in the population during their lifetimes. It is an illness that can have a severe impact on the sense of self of people affected. It is the purpose of this thesis to examine the processes by which such a sense of self is disrupted, rebuilt and maintained in people diagnosed with schizophrenia. Twelve people diagnosed with schizophrenia were interviewed with regards to the ongoing impact of their illness. In particular, interviews focused on processes relevant to their sense of identity before, during and after the diagnosis of schizophrenia. The thesis also thematises issues of power and social structure surrounding the person diagnosed with schizophrenia. It was found that, after medication, a number of social processes were important to rebuilding a sense of identity. These included the development of illness narratives, interaction with family and friends, illness management, life management, the setting of life goals and, in some cases, participation in organised religion. Identity was typically maintained through processes of stigma concealment and passing. The influence of psychiatrists, psychopharmaceutical companies and a deinstitutionalised environment in which severe mental illness is treated all emerged as significant factors in the process of rebuilding a sense of identity. The thesis seeks to make contributions to the sociology of schizophrenia and severe mental health concerns more widely. In particular, it deploys concepts of biographical crisis to make sense of the intensity of identity disruption people diagnosed with schizophrenia may experience. It also seeks to revise the perspectives of symbolic interactionism and phenomenology to better understand the emotive and embodied nature of identity processes in schizophrenia. Beyond this, the thesis explores the relationship between language, power and agency and its significance in shaping the experience of the patient diagnosed with schizophrenia. The concept of negotiated power networks is put forward to help make sense of these power relationships in a deinstitutionalised environment. Finally, the thesis proposes the concept of identity work as a way of understanding the operations of agency and relevant processes affecting identity